Polyol metabolism by Rhizobium trifolii. - Primrose, S B (1980)
In Rhizobium trifolii 7000, the polyols myo-inositol, xylitol, ribitol, D-arabitol, D-mannitol, D-sorbital, and dulcitol are metabolized by inducible nicotinamide adenine dinucleotide-dependent polyol dehydrogenases. Five different polyol dehydrogenases were recognized: inositol dehydrogenase, specific for inositil; ribitol dehydrogenase, specific for ribitol; D-arabitol dehydrogenase, which oxidized D-arabitol, D-mannitol, and D-sorbitol; xylitol dehydrogenase, which oxidized xylitol and D-sorbitol; and dulcitol dehydrogenase, which oxidized dulcitol, ribitol, xylitol, and sorbitol. Apart from inositil and xylitol, all of the polyols induced more than one polyol dehydrogenase and polyol transport system, but the heterologous polyol dehydrogenases and polyol transport systems were not coordinately induced by a particular polyol. With the exception of xylitol, all of the polyols tested served as growth substrates. A mutant of trifolii 7000, which was constitutive for dulcitol dehydrogenase, could also grow on xylitol.